Comparative Analysis of Systemic Immune Inϐlammatory Index in Acute Tonsillitis and Peritonsillar Abscess - Ahmet Koder; Yelda Ceren Orhan; Saffet Kılıçaslan; Abitter Yücel (ENT Updates, 2024)
This study aimed to investigate the utility of the Systemic Immune Inflammatory Index (SIII) as a diagnostic biomarker for distinguishing between acute tonsillitis and peritonsillar abscess. Conducted retrospectively at Trakya University, the study analyzed 122 cases of acute tonsillitis and 124 cases of peritonsillar abscess, using data from patients treated at the university's Otorhinolaryngology Department between 2013 and 2023. Ethical approval was obtained from the institution's Ethics Committee. Blood samples were evaluated to assess three key parameters: neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and SIII. Results demonstrated a significant difference in SIII values, with patients suffering from peritonsillar abscess showing significantly higher SIII levels compared to those with acute tonsillitis. Similarly, PLR values were significantly different between the groups, reinforcing the clinical relevance of these markers. In contrast, NLR did not show a statistically significant difference. These findings highlight the potential of SIII as a valuable biomarker for distinguishing between acute tonsillitis and peritonsillar abscess, offering promising applications in otolaryngology to enhance diagnostic accuracy and inform treatment decisions.